Disaster science and management - Bhattacharya, Tushar (McGraw-Hill's AccessEngineering., 2012)
"Disaster Science and Management has been written based on an extensive library research and with an empirical insight on response to disasters in various cultural and social contexts in India. The book has essentially six components: understanding of disasters and their relationship with human development; the international code of conduct and minimum standard of humanitarian response; the science of disasters; the Government of India's efforts in minimizing disaster losses; management of disasters; and real life case studies of responses after disasters, including disaster risk reduction by the poor and vulnerable. Disaster Management has become an integral part of the curriculum in Engineering, Management, Social science, Economics and Rural Development Courses in India. The book has several examples of "good and not so good" practices of all stage of the disaster management cycle which comes from the experiential perspective the author has gained through his involvement in managing most types of disasters. Policy makers, executioners and the academia will find this book useful as there is no dichotomy between development and disaster management; both attempt to improve peoples' abilities to absorb macro and micro shocks.".